Selective Monitoring of the Enzymatic Activity of the Tumor Suppressor Fhit1. Issue 38 (5th August 2014) - Hacker, Stephan M.; Mortensen, Franziska; Scheffner, Martin; Marx, Andreas
Abstract Cancer is a leading cause of death worldwide. Functional inactivation of tumor suppressor proteins, mainly by mutations in the corresponding genes, is a key event in cancer development. The fragile histidine triade protein (Fhit) is a tumor suppressor that is frequently affected in different cancer types. Fhit possesses diadenosine triphosphate hydrolase activity, but although reduction of its enzymatic activity appears to be important for exerting its tumor suppressor function, the regulation of Fhit activity is poorly understood. Here, we introduce a novel fluorogenic probe that is suited to selectively analyze the enzymatic activity of Fhit in extracts derived from human cells. This novel method will allow in‐depth insight into the mechanisms involved in Fhit regulation in biologically relevant setups and, thus, into its role in the development of cancer.